Community Exercise: A New Tool for Personalized Parkinson’s Care or Just an Addition to Formal Care? - Domingos, Josefa; Dean, John; Fernandes, Júlio Belo; Massano, João; Godinho, Catarina (Frontiers in Systems Neuroscience, 2022)
Physiotherapy and exercise are associated with motor and non-motor benefits in Parkinson´s disease. Community exercise programs may increase ongoing exercise participation and help people with Parkinson´s disease actively participate in their health management. But there is still limited knowledge about these programs regarding their benefits, safety, implications over the long-term, and effective implementation. These questions could hold relevant clinical implications. In this perspective article, we identify the current challenges and reflect upon potential solutions to help community exercise to be implemented as an additional anchor to personalize management models in Parkinson´s disease.